BIBLIOMETRIC ANALYSIS OF SHARIAH COMPLIANT CAPITAL ASSET PRICING MODELS - Touti, Nihal; Alaoui Taïb, Asmâa (Journal of Islamic Monetary Economics and Finance, 2023)
This study conducts a bibliometric analysis of the literature on shariah compliant asset pricing based on Scopus-indexed publications. The data on publications are collected employing a search string encompassing various keywords related to Islamic finance and asset pricing.  Simple statistical techniques are applied, complemented by the utilization of VOS viewer software to analyze document trends by year, country, source, and patterns of collaboration among authors, co-citations, and keywords co-occurrence. The bibliometric analysis reveals a proliferation of publications across 127 journals, with the Pacific Basin Finance Journal being the most prominent. Collaboration among authors spans 56 countries, with Malaysia emerging as a key contributor. Notably, keywords like "Islamic finance" and "Shariah-compliant" have seen increased importance in recent years. The statistical results demonstrate a substantial surge in Scopus-indexed publications related to Shariah-compliant compliant Capital Asset Pricing Models, particularly in the past five years, reflecting the growing popularity and research opportunities within Islamic finance and asset pricing.